PTU-002 Achieving biochemical remission in crohn's disease with adalimumab therapy utilsing therapeutic drug monitoring. (8th June 2018) - Plevris, Nikolas; Jenkinson, Phil; Lyons, Matthew; Jones, Gareth; Chuah, Cher; Hall, Rebecca; Deekae, Adepeju; Merchant, Lynne; Pattenden, Rebecca; Din, Shahida; Watson, Eleanor; Shand, Alan; et al.
Abstract : Introduction: Adalimumab (ADA) is a well-established treatment for Crohn's disease (CD). Despite this limited data are available regarding the relationship of serum ADA levels, and antibodies to ADA (ATA) with clinical outcomes. Methods: We performed a prospective cross-sectional study to investigate the association of serum ADA levels and ATA on clinical outcomes. Inclusion criteria were a diagnosis of CD and minimum of 12 weeks therapy. Patients were written to in advance of their next clinic visit and advised to omit their ADA dose if due within 72 hour from their appointment. Harvey Bradshaw Index (HBI), serum ADA levels/ATA, CRP and faecal calprotectin (FC) were simultaneously collected at clinic. Biochemical remission was defined as FC <200 µg/g in addition to CRP <5 mg/L. Results: At the time of drug level testing, 259 patients were on ADA maintenance therapy. A total of 195 samples were available for analysis from 178 patients; matched HBI, FC and CRP were available for 171 patients. Median duration of ADA therapy was 2.4 years (IQR 1.2–4.3) with 37/178 (20.8%) patients receiving concomitant immunosuppression. Median ADA levels were higher in patients receiving weekly (n=55) (14.0 µg/ml, 8.0–17.4) vs. fortnightly dosing (n=123) (11.0 µg/ml, 7.0–14.5, p=0.0095). 29/178 (16.3%) patients were positive for ATA. A clear negative correlation was observed between ADA levels and ATA (Spearman's r=−0.567, p<0.0001). Median ADA levels were 11.4 µg/ml (8.0–15.0), 5.0 µg/ml (4.0–6–6) and 1.0 µg/ml (0.8–2.0) at ATA of <10 AU/ml, 10–50 AU/ml and >50 AU/ml, respectively (p<0.0001). Patients in biochemical remission (n=81/171; 47.4%) had significantly higher ADA levels (12.0 µg/ml, 10.0–15.7) than those with active disease (8.0 µg/ml, 4.8–12.5, p<0.0001). ROC analysis revealed a positive correlation between ADA levels and biochemical remission [AUC (95% CI) 0.71 (0.63–0.79), p<0.0001]. An optimum ADA level of >8.8 µg/ml was identified for predicting biochemical remission (82.7% sens, 55.6% spec, positive LR 1.86). ADA levels but not ATA independently predicted biochemical remission in a multivariate logistic regression model. Conclusions: Higher ADA levels were independently associated with biochemical remission; levels of >8.8 µg/ml, higher than previously suggested, might be an appropriate target in the maintenance treatment of CD.